Investigations on the influence of particle reinforcement and wire materials on the surface quality and machining characteristics of AA6061-TiB2 alloy in WEDM. (27th August 2021) - Ramraji, K; Rajkumar, K; Selvakumar, G; S, Ram Prakash
Abstract: In this research, the significance of particle reinforcement and the effect of wire materials on machining of AA6061-TiB2 composite by Wire Electrical Discharge Machining (WEDM) was investigated. Stir cast AA6061–TiB2 (varying 5, 10, and 15 wt.%) was used as the work material for this present study owing to its superior mechanical properties and profound applications. WEDM is the most viable cutting process to produce intricate shapes and sharp corners with good surface texture. Taguchi methodology was used to conduct the experiments. Phase constituents of the work material were observed using XRD analysis. The results revealed that aluminium and titanium diboride are the major phase constituents without any reaction phases. Metallographic analysis was conducted to figure out the erosion mechanism and crater formation during spark discharge. The experimentation reveals that the percentage of particle reinforcement was the dominating factor in surface quality (62.04%) and machinability (34.2%). The TiB2 (5 wt.%) reinforced composite exhibits excellent machinability and surface quality. Furthermore, in terms of machining rate, zinc-coated brass wire performs better than plain brass wire. Contrastingly, plain brass wire exhibits superior surface quality. In addition to that multi-objective optimization was performed using desirability analysis to achieve higher material removal rate and lower surface roughness. After the confirmation test, it is seen that the experimental values are in close agreement with the estimated values.